Sulfonamide Allergies - Amber Giles; Jaime Foushee; Evan Lantz; Giuseppe Gumina (MDPI AG, 2019)
As one of the earliest developed antimicrobial classes, sulfonamides remain important therapeutic options for the empiric and definitive treatment of various infectious diseases. In the general population, approximately 3−8% of patients are reported to experience a sulfonamide allergy. Sulfonamide allergies can result in various physical manifestations; however, rash is reported as the most frequently observed. In patients with human immunodeficiency virus (HIV), dermatologic reactions to sulfonamide antimicrobial agents occur 10 to 20 times more frequently compared to immunocompetent patients. This article describes the incidence, manifestations, and risk factors associated with sulfonamide allergies. The potential for cross-reactivity of allergies to sulfonamide antimicrobials with nonantimicrobial sulfonamide medications is also reviewed. Data suggest that substitutions at the N1 and N4 positions are the primary determinants of drug allergy instead of the common sulfonamide moiety. For patients with an indication for a sulfonamide antimicrobial with a listed allergy, it is important for healthcare practitioners to adequately assess the allergic reaction to determine appropriate management. Rechallenge and desensitization strategies may be appropriate for patients with delayed maculopapular eruptions, while alternative treatment options may be prudent for more severe reactions. Available data suggests a low risk of cross-allergenicity between sulfonamide antimicrobial and nonantimicrobial agents.